On the Experience and Representation of Space (Existential Analysis: Journal of the Society for Existential Analysis, 1998)
This paper looks at the phenomenon of space primarily from an Existential-phenomenological perspective. Its focus is on our everyday experience of space, and this is referred to as the ontic dimension of experience. The relationship between the ontic dimension and the ontological dimension, which refers to the underlying nature of our being-in-the-world, is examined. Ontologically it is more accurate to consider our nature as being spatial rather than being in space or having space inside us. These ideas are then applied to the conditions of Claustrophobia and Agoraphobia. It is suggested that they are best understood not as pathological states but as the ontic equivalents of our ontologically unsupported status in the world and are particular ways of solving the existential dilemma of how to be in-the-world, or spatial. It is suggested however that personal developmental history can influence the likelihood that one person complain of the conditions and another not. An Existential-phenomenological understanding of space is compared with a Psychoanalytic understanding of space.